Minimum wages and racial discrimination in hiring: Evidence from a field experiment - Alec Brandon; Justin E. Holz; Andrew Simon; Haruka Uchida (W.E. Upjohn Institute for Employment Research, 2023)
When minimum wages increase, employers may respond to the regulatory burdens by substituting away from disadvantaged workers. We test this hypothesis using a correspondence study with 35,000 applications around ex-ante uncertain minimum wage increases in three U.S. states. Before the increases, applicants with distinctively Black names were 19 percent less likely to receive a callback than equivalent applicants with distinctively white names. Announcements of minimum wage hikes substantially reduce callbacks for all applicants but shrink the racial callback gap by 80 percent. Racial inequality decreases because firms disproportionately reduce callbacks to lower-quality white applicants who benefited from discrimination under lower minimum wages.
Keywords: J23; C93; J71; J15; 330; minimum wage; correspondence study; racial discrimination